Sustainable Civilization - Klaas Van Egmond (Palgrave Macmillan, 2014)
Western civilization has entered a new fundamental crisis that can be explained by a very one-sided orientation of social values based on materialism and egocentrism, which is disrupting the delicate balance between the opposing forces of 'mind' and 'matter', and of 'I' and 'the others'. Many sources – from the great works of philosophy, religion, art and culture to social surveys and the course of history – qualify sustainability as the dynamic equilibrium between fundamental opposing forces. This insight and the ethical ability to better discriminate between stabilizing and destabilizing forces would allow further justification of human rights and new institutional arrangements in society at large and, in particular, in politics, economy and finance. It would enable a sustainable civilization to flourish within the boundaries of freedom and human dignity